Gel formulations containing Sumbawa's horse milk with carbomer gel base - Dian Ermawati; Uswatun Chasanah; Herika Juli Andani; Khalda Nisrina (Universitas Muhammadiyah Malang, 2019)
Peptides from Sumbawa horse milk are active as antibacterial and antioxidant. Horse milk has a higher content of vitamin C than cow or goat's milk, and cream products that contain milk can overcome dry skin. The Gel is one of the topical dosage forms suitable for acne medications and oily skin types. This study aimed to determine the effect of variations in horse milk content formulated in gel preparations with carbomer 1% base as gelling agents on physical characteristics (organoleptic, viscosity, pH) and antibacterial activity in Propionibacterium acnes. In this study, gel preparations were made with six different formulas on horse milk content, namely FI (2.5%), FII (5%), and FIII (10%), FIV (15%), FV (20%), and FVI (25%) with 1% carbomer base on each formula and well method were used for the antibacterial test. From the organoleptic test, it was found that in all of the gel formula had soft textured, thick white color, and distinctive aroma like horse milk. The viscosity test showed that was no significant difference, but the pH test showed a significant difference for each formula. In this study showed that all of the gel formulae did not have an inhibitory zone, which means that at each level there was no evidence of antibacterial activity in the P. acnes. So, it could be concluded that all gel formula had good gel characteristics but there was no inhibitory activity against the P. acnes.